El mejor de los mundos en la teología racionalista musulmana clásica - Escobar Gómez, Santiago (Anales del Seminario de Historia de la Filosofía, 2005)
An introduction, from an al-Ghazâlî´s text, into a philosophic theodicy and an Arabic rationalistic theology (mu`tazili). Both of them, theology and philosophy, belive that God has created the best of possible worlds, so that, this world is optimistic and deterministic. However this optimism sense has different causes in them; for theodicy that is owing to Good wishes, while for philosophy is because of the causality and logical necessity.
Keywords: Racionalismo; Necesidad; Lógica; Determinismo; Voluntad; Optimismo; Teodicea; Causalidad; Justicia